Requisitos para la certificación de productos orgánicos peruanos para la exportación - Miranda Ramos, Edwar Alexander (2016)
The present work has been prepared by information originated from an International Certification Institution, as well as the originated one from search and studies in production and merchandising in our country that is provided with a production system in charge of small producers who do not use agrochemicals, irradiation, harmful additives, and whose production fulfils the requests of the market of organic products. It is so the target, in a context of increasing interest to obtain a certificate of organic production to export our products in Peru, is to announce the producers, companies and marketers the Requirements for Certification of Peruvian Vegetables Organic Products for Export. The material used in the investigation to collect and to obtain the necessary information, involves from books, thesis, magazines, web sites, and using the Deductive Inductive Method, starting with the compilation and analysis of precedents with regard to studies and cases of exports of organic products, continuing to identify the information target for the development of the thesis focus in the obtained information on certification of organic production in Peruvian products, to then process information from consultations bibliographical, web sites, virtual material, norms and technical regulations. The obtained information recounts that for Peruvian vegetables products are certified as organics, the requirements to consider focusing on the Seeds that will have to come from a production without treatment of chemical disinfection o with synthetic products; also, the ground that must be treated by organic fertilizer (animal dung and vegetable remains of the same establishment); for the plagues handling, it prohibits the use of herbicides, fungicides, insecticides, application of irradiation, microwaves, both the prevention, control and storage; and the last requirement is that it must pass for a Transitional Period. Finally the certifying company issues the certificate of organic production to the farmers, companies and marketers.